Alternatives to Randomized Control Trials: A Review of Three Quasi-experimental Designs for Causal Inference - Panko, Pavel (2015)
Abstract. The Randomized Control Trial (RCT) design is typically seen as the gold standard in psychological research. As it is not always possible to conform to RCT specifications, many studies are conducted in the quasi-experimental framework. Although quasi-experimental designs are considered less preferable to RCTs, with guidance they can produce inferences which are just as valid. In this paper, the authors present 3 quasi-experimental designs which are viable alternatives to RCT designs. These designs are Regression Point Displacement (RPD), Regression Discontinuity (RD), and Propensity Score Matching (PSM). Additionally, the authors outline several notable methodological improvements to use with these designs.